Identification of a Novel Ryanodine Receptor Mutation Causing Malignant Hyperthermia. (7th November 2013) - Valaskova, Iveta; Dudova, Silvie; Necasova, Jana; Ostadalova, Edita; Vanaskova, Martina; Stepankova, Dagmar; Schröderova, Ivana; Gaillyova, Renata; Kuglik, Petr
Abstract : Malignant hyperthermia (MH) is a potentially fatal autosomal dominant disorder of the skeletal muscle and is triggered in susceptible individuals by commonly used inhalation anaesthetics and depolarizing muscle relaxants. Around 80% of the affected family are linked to the ryanodine receptor ( RYR1 ) gene. More than 300 mutations in RYR1 have been associated with the MH-susceptible phenotype. Here we report the identification by two independent methods of a novel mutation associated with the MH-susceptible phenotype in the RYR1 gene.